2005
DOI: 10.1007/s00415-005-0673-7
|View full text |Cite
|
Sign up to set email alerts
|

Upper cranial nerve palsy resulting from spontaneous carotid dissection

Abstract: ICA dissection must be included in the differential diagnosis of upper cranial nerve palsy and should be assessed by duplex ultrasound and magnetic resonance imaging. A possible explanation is nerve ischemia due to a transient or permanent interruption of the blood supply by compression of the vasa nervorum originating from the intracranial carotid artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Local symptoms, especially lower cranial nerves palsies, are traditionally explained by the compressive effect of an enlarged carotid artery, and therefore, thought to be associated with DAs [16]. In addition, hypoperfusion due to an impaired or compressed vasa nervorum has been discussed as a potential cause of cranial nerve palsies [17]. In the present study, we found similar rates for Horner's syndrome, cranial nerve palsies, and tinnitus when comparing the groups.…”
Section: Symptomssupporting
confidence: 76%
See 1 more Smart Citation
“…Local symptoms, especially lower cranial nerves palsies, are traditionally explained by the compressive effect of an enlarged carotid artery, and therefore, thought to be associated with DAs [16]. In addition, hypoperfusion due to an impaired or compressed vasa nervorum has been discussed as a potential cause of cranial nerve palsies [17]. In the present study, we found similar rates for Horner's syndrome, cranial nerve palsies, and tinnitus when comparing the groups.…”
Section: Symptomssupporting
confidence: 76%
“…However, the lower rate of ischemic stroke after correction for the degree of stenosis in our secondary analysis (Figure 4) contradicts this reasoning. One could postulate that we are dealing with two facets of the same pathophysiological process and that mechanical factors, namely the characteristics and the size of the initial tear, the shape of the intramural hematoma, an increased vessel caliber, or different pathomechanisms, such as the primary rupture of the vasa vasorum, may be the main difference between aneurysmal and non-aneurysmal SCADs, leading to the lower rate of ischemic strokes we have seen in our data [17].…”
Section: Symptomsmentioning
confidence: 84%
“…Cervical artery dissection (CeAD) causes ischemic stroke, Horner syndrome and/or multiple cranial nerve palsies, usually involving the lower cranial nerves [ 3 ]. However, there has been several reports of upper cranial nerve palsy resulting from spontaneous internal carotid artery (ICA) dissections [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) Eine Druckparese durch die lokale Raumforderung des H ä matoms, vor allem, wenn sich das intramurale H ä matom in den Sinus cavernosus ausbreitet [53,55,56] . 2Eine isch ä mische L ä sion der Hirnnerven durch Verschluss der Vasa nervorum als Folge der Karotisdissektion [57] . Ein pulssynchroner Tinnitus, der wahrscheinlich durch fortgeleitete Turbulenzen des Blutstroms an der ACI Stenose entsteht, wird in 16 -27 % der F ä lle berichtet und kann auch ein Zeichen einer beginnenden Rekanalisation einer initial verschlossenen Arterie sein [49,52,58] .…”
Section: ▼ Klinische Befunde Spontane Und Traumatische Dissektionenunclassified